Curved Holographic Augmented Reality Near-Eye Display System Based on Freeform Holographic Optical Element with Extended Field of View - Hong Xu; Yuan Xu; Changyu Wang; Juan Liu (Photonics)
At present, most near-eye display devices adopt flat substrates, which have problems such as limited field of view (FOV) and bulky shape, while the curved structure is expected to expand the FOV with appropriate volume. In this paper, we propose a curved holographic augmented reality (AR) near-eye display system based on holographic optical element (HOE) with the ability to expand the FOV. The system includes a display source and a HOE with curved substrate. We analyze the system by exploiting the diffraction theory between plane and curved surface, and a layered and weighted FOV optimization method using particle swarm optimization algorithm is proposed to realize the optimization of the phase of freeform HOE. Numerical and experimental results show that the proposed curved holographic near-eye display system can realize cylindrical AR display and expand the FOV of the system. It is expected to be applied to the holographic AR near-eye display in the future.